Spatio-temporal processes in autophagosome-lysosome fusion - Liu Shizuo; Yan Huan; Diao Jiajie; Zhang Shen; Zhong Qing (Medical Review)
Macroautophagy/autophagy is a lysosome-dependent degradation process involved in cellular energy metabolism, recycling and quality control. Autophagy is a highly dynamic and precisely regulated process, which contains four major steps: autophagic membrane initiation and cargo recognition, autophagosome formation, autophagosome-lysosome fusion and lysosomal degradation. During the terminal phase of autophagy, the merging of the autophagosome and lysosome membranes is critical for the effective breakdown of sequestered cargoes. However, the participated molecules and the interplay among them have not been fully uncovered. The spatiotemporal property of these molecules is crucial for maintaining the orderly fusion of autophagosomes and lysosomes, otherwise it may lead to fusion disorders. In this article, we tend to summarize the molecules mediating autophagosome-lysosome fusion into two categories: effector molecules and regulatory molecules. The effector molecules are soluble N-ethylmaleimide–sensitive factor attachment protein receptor and tethering proteins, and the latter category contains phosphatidylinositol, Rab GTPases and ATG8-family proteins. The spatio-temporal properties of these autophagosome-lysosome fusion mediating molecules will be featured in this review.